How to Dwell in Garbage Patches? Waste Communities in the Aftermath of Ancestral Catastrophe in Chen Qiufan’s The Waste Tide (2013) and Wu Ming-yi’s The Man with the Compound Eyes (2011) - Borowski, Mateusz (Text Matters: A Journal of Literature, Theory and Culture, 2024)
The article approaches the problem of dwelling in areas affected by environmental crises through the lens of two speculative fabulations. Chen Qiufan’s The Waste Tide (2013) and Wu Ming-yi’s The Man with the Compound Eyes (2011) both depict the intrusion of human-induced catastrophes into the life of coastline communities in Southeast Asia, requiring them to work out forms of dwelling and remembering that make space for the assemblages of beings that emerge out of the devastated landscapes inherited after the modern era. Each of the novels tackles a different aspect of this problem. The Waste Tide shows the catastrophic effects of mass production and recycling of electronic garbage which, shipped to junkyards in the Global South, not only exacerbates the environmental pollution, but also exerts a negative impact on the local indigenous and migrant communities, threatening their economic status and social cohesion. Inspired by Martin Heidegger’s meditations on poetic dwelling, The Man with the Compound Eyes features the so-called Great Pacific Garbage Patch, a gigantic collection of plastic waste gathering on the surface of the ocean and hitting coastal regions, wreaking havoc on local life. By investigating the two novels, I look for models of remembering and dwelling together that go beyond the anthropocentric notion of memory rooted in an individual self and offer new models of dwelling in times of catastrophe.